Effectiveness of physio-cognitive dual-task training on improving global cognition, health-related quality of life, and physical outcomes among older adults with neurocognitive disorders: an umbrella review. - Chern, Calvin Wei Jie; Cheng, Ling Jie; Chiang, Glenys Shu Wen; Yap, Siat Yee; Giang, Thuy Anh; Lau, Siew Tiang (Age & Ageing, 2026)
Background Physio-cognitive dual-task training (PCDT), combining physical and cognitive tasks, is a promising approach. However, clarity regarding its effectiveness and evidence credibility remains limited. Objective To evaluate PCDT effectiveness on global cognition, health-related quality of life, and physical outcomes (activities of daily living, gait, balance) in older adults with neurocognitive disorders, assess review quality and evidence certainty, and explore moderator effects. Methods Eight databases and grey literature were searched to 31 December 2024. Two reviewers independently screened, extracted data, and assessed review quality (AMSTAR-2) and evidence certainty (GRADE). Meta-level and study-level meta-analyses were conducted. Subgroup analyses and meta-regression explored moderator effects. PROSPERO: CRD42024622115. Results Seventeen reviews with 47 unique meta-analyses involving 81 unique studies were included. Meta-level analyses indicated small significant improvements across outcomes except health-related quality of life. Study-level analyses, correcting for overlapping primary studies, confirmed significant benefits for global cognition and health-related quality of life; however, physical outcome effects were non-significant. Prediction intervals for all outcomes were non-significant. Simultaneous PCDT and higher weekly frequency showed greater benefits. Participants with dementia benefited less than those with mild cognitive impairment. Age was not a significant moderator. Most reviews were low or critically low quality, and evidence certainty was low. Conclusions PCDT is potentially associated with improvements in cognitive, physical, and quality-of-life outcomes among older adults with neurocognitive disorders. However, prediction intervals suggest effectiveness uncertainty, and heavy sample weighting toward prodromal stages warrants caution. PCDT may not be indicated for cognitive improvement in established dementia. High-quality reviews are urgently needed.